Development of an Android mobile application for cycle users of the city of Bogotá D.C. (2017)
This article is about the development of an application for smartphone phones with Android operating system for cycle route who transit in the city of Bogota D.C. The development of the project was achieved with the help of a methodological process, which was structured in four phases, these phases are described: the general context of applications developed in Android, needs identification of cyclical, mobile application development, validation and results; The coupling of these stages allowed to analyze the current situation and to design, program and implement an application according to the needs of the study population, in order to encourage the use of the bicycle as a means of transport for sustainable mobility. The application developed includes the following functionalities: georeferenced maps of the network of cycle route and bicycle route of the city of Bogota, by selecting a source point and a destination point a route is generated, which is drawn on a map, which has in The possibility of users having information on the status of the cycle route through the qualification of the state of the road, lighting and signaling, search for parking cycle, creation of public or private points of interest such as bicycle stores, Workshops of repair, hydration points, among others, history of the route made with information of the time spent in making the route and access to the information of events and tips.